Rastreamento da capacidade de imitar de bebês de 12 a 24 meses do desenvolvimento típico - Abreu, Silmara Soares de (2016)
This study aimed to develop a simple tool for tracking the ability to imitate in children from 12 to 24 months of age. Considering that learning occurs through processes where the human being learns to observe each other and from there go to imitate him, this process plays an important role in socio-cognitive skills as well as the linguistic and social learning of the child. Therefore, it is desirable that losses in this skill are detected as early as possible so that intervention actions are initiated. For this, we rely on an assessment tool known as Rasch measurement model, and built a simple to operate indicating the skills to imitate young children under the command of an adult. Our sample consisted of 65 children of typical development, aged 12 to 24 months in two private institutions. Our results showed that 62 were able to mimic the commands in varying scales, but 3 children did not imitate any of the commands shown by the adult. These data suggest that this instrument can be used by the teacher in the classroom in order to assess possible changes in the development of young children have very early, or even serve as a complement to professional experts time to review with the patient.